A Phase 1 Drug‐Drug Interaction Study Between Brigatinib and the CYP3A Substrate Midazolam in Patients With ALK‐Positive or ROS1‐Positive Solid Tumors. (27th January 2023) - Hanley, Michael J.; D'Arcangelo, Manolo; Felip, Enriqueta; Garrido, Pilar; Zhu, Jiaxi; Ye, Meng; Vranceanu, Florin; Gupta, Neeraj
Abstract: Brigatinib is a next‐generation anaplastic lymphoma kinase (ALK) inhibitor approved for the treatment of patients with ALK ‐positive ( ALK +) non–small cell lung cancer (NSCLC). A phase 1 drug‐drug interaction study was conducted to evaluate the effect of multiple‐dose administration of brigatinib on the single‐dose pharmacokinetics of midazolam, a sensitive cytochrome P450 3A substrate. In cycle 1, patients with ALK + or ROS1 + solid tumors, including NSCLC, received a single 3‐mg dose of midazolam as an oral solution alone on day 1 and then coadministered with brigatinib on day 21 (brigatinib 90 mg once daily on days 2‐8; 180 mg once daily on days 9‐28). After cycle 1, patients could continue to receive brigatinib in 28‐day treatment cycles. The primary study objective was to characterize the effect of brigatinib 180 mg once daily on midazolam pharmacokinetics. The secondary objective was to assess safety. Exploratory efficacy endpoints included objective response rate and progression‐free survival. Brigatinib was generally well tolerated, and safety data were consistent with the known safety profile. Among the 10 patients with ALK + NSCLC, the confirmed objective response rate was 30% and median progression‐free survival was 7.2 months. Coadministration of brigatinib reduced midazolam maximum observed plasma concentration by ≈16% (geometric least‐squares mean ratio, 0.836 [90%CI, 0.662‐1.056]) and area under the plasma concentration–time curve from time 0 to infinity by ≈26% (geometric least‐squares mean ratio, 0.741 [90%CI, 0.600‐0.915]). Thus, brigatinib is a weak inducer of cytochrome P450 3A in vivo.